2018
DOI: 10.3928/1081597x-20180823-02
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Posterior Corneal Features Between Normal Corneas and Subclinical Keratoconus

Abstract: PURPOSE: To compare posterior corneal features and their discriminating power for differentiating normal corneas from subclinical keratoconus using the Placido dual-Scheimpflug analyzer. METHODS: Patients were retrospectively included in the study. The preoperative normal right eyes of 79 patients imaged with a Placido dual-Scheimpflug system and with a stable postoperative LASIK follow-up of a minimum of 36 months were included in the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…The clinical symptoms in these twins were very typical and consistent, including corneal ectasia, thinning, superficial scarring, and a cone-shaped protrusion with Vogt’s striae, Fleischer’s ring, and Munson’s sign. Their parents’ symptoms were not pronounced enough to diagnose KC, but they did present some subclinical manifestations, including larger corneal curvatures, back elevation, and thinner corneal thickness compared to normal, unrelated individuals [ 29 31 ]. These complex clinical manifestations in this family supported the hypothesis of a polygenic inheritance pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms in these twins were very typical and consistent, including corneal ectasia, thinning, superficial scarring, and a cone-shaped protrusion with Vogt’s striae, Fleischer’s ring, and Munson’s sign. Their parents’ symptoms were not pronounced enough to diagnose KC, but they did present some subclinical manifestations, including larger corneal curvatures, back elevation, and thinner corneal thickness compared to normal, unrelated individuals [ 29 31 ]. These complex clinical manifestations in this family supported the hypothesis of a polygenic inheritance pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the posterior corneal elevation had a relatively good discriminatory ability for subclinical KC screening and that the posterior corneal elevation difference (B_Elv-D) determined with enhanced best fit sphere was better than the posterior corneal elevation alone to diagnose subclinical KC [3, 23, 24]. Eccentricity is a corneal shape factor calculated within a central diameter of 8 mm averaged over all meridians of the corneal surface, to determine a prolate shape or an oblate shape of the corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Vorteilhaft an einer Beurteilung von posterioren Hornhautveränderungen ist die hohe Sensitivität bez. einer Differenzierung von subklinischen Keratokonusveränderungen im Vergleich zur physiologischen Hornhautkonfiguration [23]. Künftige Studien sollten daher ein breiteres Spektrum von Verlaufsparametern enthalten.…”
Section: Diskussionunclassified